Challenges in Ensuring Personal Data Protection For Society in The Era of Society 5.0: Indonesia’s Case Study - Tegar Islami Putra; Waspiah; Indriana Firdaus; Fitria Damayanti; Bintang Rafli Ananta (Universitas Negeri Semarang, 2024)
Personal data protection is crucial in realizing cybersecurity in the Industrial Revolution 5.0 era in Indonesia. The regulation of cybercrime and personal data protection is to provide protection to victims of cybercrime and provide legal sanctions to perpetrators. The implementation of this regulation is not an easy thing, there are various challenges faced, especially in order to face the Era of Society 5.0. This research utilizes normative legal research which examine all regulations (positive law, principles, and legal doctrines) that are applicable in Indonesia and will not overlook the comparison of regulations in other countries to correlate various legal behaviors resulting from the said regulations in an effort to find answers to the research questions. The results show that there are several challenges faced in ensuring personal data protection for society in the era of society 5.0 with a case study of Indonesia, including low public awareness, political patronage, and the need for competent officials hindering effective law enforcement. In addition, there are implementation challenges in the form of regulatory weaknesses that are not matched by implementing regulations and specialized agencies, low public awareness and understanding of the importance of personal data protection, lack of competence of human resources managing personal data, as well as sectoral ego and lack of moral responsibility of officials.